2005
DOI: 10.1097/01.all.0000174158.78626.35
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular aspects of anaphylaxis: implications for treatment and diagnosis

Abstract: Current evidence supports use of the supine/Trendelenburg position, epinephrine by intravenous infusion and aggressive volume resuscitation. If these fail, atropine should be considered for severe bradycardia and potent vasoconstrictors may be useful. To confirm the diagnosis of anaphylaxis, serial measurements of mast cell tryptase may be preferable to a single measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(99 citation statements)
references
References 32 publications
2
90
0
7
Order By: Relevance
“…19 A recent single-center trial described successful initial management with intravenous epinephrine infusions for anaphylaxis with hypotension, suggesting that this might be a viable strategy. 10,20 Detailed procedures for the preparation and administration of epinephrine infusions have been published. 5 It is important to recognize the potential for lethal arrhythmias when administering intravenous epinephrine, and therefore continuous cardiac monitoring is recommended.…”
Section: Epinephrinementioning
confidence: 99%
See 1 more Smart Citation
“…19 A recent single-center trial described successful initial management with intravenous epinephrine infusions for anaphylaxis with hypotension, suggesting that this might be a viable strategy. 10,20 Detailed procedures for the preparation and administration of epinephrine infusions have been published. 5 It is important to recognize the potential for lethal arrhythmias when administering intravenous epinephrine, and therefore continuous cardiac monitoring is recommended.…”
Section: Epinephrinementioning
confidence: 99%
“…20 Recent case reports and animal studies have demonstrated that vasopressin is useful when treating hemorrhagic and septic shock. The effect of vasopressin on systemic anaphylaxis has not been investigated, except in clinical case reports.…”
Section: Vasopressorsmentioning
confidence: 99%
“…During an anaphylactic reaction, serious cardiovascular or pulmonary dysfunction often leads to acute death, with severe hypotension as the cardinal clinical feature. Intravenous fluids and parenteral adrenaline administration are considered the only effective treatment; unfortunately, severe cardiovascular collapse during anaphylaxis is often resistant to this treatment (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…anaphylactic shock; hepatic circulation; portal hypertension; splanchnic congestion ANAPHYLACTIC HYPOTENSION appears to be caused primarily by a decrease in blood flow to the heart, because left ventricular function is relatively well preserved during anaphylactic shock (1,2). Peripheral circulatory collapse is ascribed to hypovolemia, which results from a decrease in effective circulating blood volume.…”
mentioning
confidence: 99%